OTIMIZAÇÃO DA FROTA MECANIZADA EM FUNÇÃO DA ÁREA CULTIVADA NO INÍCIO DO PROGRAMA BRASILEIRO DE BIOENERGIA (PRO-ÁLCOOL) - Stolf, Rubismar; Oliveira, Ana Paula Rodrigues de (ENERGIA NA AGRICULTURA, 2023)
OPTIMIZATION OF MECHANIZED FLEET AS A FUNCTION OF CULTIVATED AREA AT THE BEGINNING OF THE BIOENERGY BRAZILIAN PROGRAM (PRO-ALCOOL) RUBISMAR STOLF1, ANA PAULA RODRIGUES DE OLIVEIRA2 1 Department of Natural Resources and Environmental Protection, Federal University of São Carlos, Brazil, Full Professor, Senior. Email: stolfrubismar@gmail.com 2 Technology Department (IT), Brazil Bank, Brasilia, Brazil, Master's student in Agroecology and Rural Development-UFSCar. E-mail: anaprdo@hotmail.com ABSTRACT: In the 1960s, due to the US-Cuba crisis, Cuba, its largest supplier, lost the US sugar market. The Brazilian government has developed a strategy to occupy part of this market through the Sugar and Alcohol Institute (IAA), which took several actions to moderni the sugar and alcohol agroindustry. This strategy was the basis for the national biofuel alcohol production program (Proalcool) in 1975. Ethanol jumped from 0.6 to 3.4 billion liters from 1975 to 1979/80, significantly exceeding the production target. This feat stimulated the Planalsucar (IAA) research to conduct an extensive survey of the fleet of agricultural machinery and implements in 67 units. The general aim of the present paper was to provide a historical record of this unedited survey database. The specific goal was to analyze the variation in the number of tractors and implements per thousand ha as a function of the sugarcane planting area to study the optimization of equipment use. We determined the linear correlation coefficient and the regression equation for each device. All significant correlation coefficients showed a decrease in the number of machines and implements per 1,000 ha related to cultivated area as follows: the number of tire tractors, total power of tire tractors (kW), harrows, plowers, furrows, loaders, and cultivators (cultivating implements). In other words, the larger the property is, the smaller the need for tractors and implements per unit area. This work provided evidence of the performance of a process of the economy of scale in the sugarcane production system. Keywords: mechanized fleet survey; economy-of-scale; sugarcane OTIMIZAÇÃO DA FROTA MECANIZADA EM FUNÇÃO DA ÁREA CULTIVADA NO INÍCIO DO PROGRAMA BRASILEIRO DE BIOENERGIA (PRO-ÁLCOOL) RESUMO: Na década de 1960, devido à crise EUA-Cuba, este, seu maior fornecedor, perdeu o mercado norte-americano de açúcar. O governo brasileiro desenvolveu uma estratégia para ocupar parte desse mercado por meio do Instituto do Açúcar e do Álcool (IAA), que realizou diversas ações para levar à modernização da agroindústria sucroalcooleira. Essa estratégia foi a base do Programa Nacional de Produção de Álcool Biocombustível (Proálcool) em 1975. O etanol saltou de 0,6 para 3,4 bilhões de litros de 1975 a 1979/80, superando significativamente a meta de produção. O feito estimulou a pesquisa do Planalsucar (IAA) a realizar um amplo levantamento da frota de máquinas e implementos agrícolas em 67 unidades. O objetivo geral do presente artigo foi fornecer um registro histórico desse banco de dados de pesquisa não editado. O objetivo específico foi analisar a variação do número de tratores e implementos por mil ha em função da área de plantio de cana-de-açúcar para estudar a otimização do uso dos equipamentos. Determinamos o coeficiente de correlação linear e a equação de regressão para cada dispositivo. Todos os coeficientes de correlação significativos mostraram uma diminuição no número de máquinas e implementos por 1.000 ha em relação à área cultivada da seguinte forma: número de tratores de pneus, potência total dos tratores de pneus (kW), grades, arados, sulcadores, carregadeiras e cultivadores (implementos de cultivo). Ou seja, quanto maior a propriedade, menor a necessidade de tratores e implementos por unidade de área. Este trabalho forneceu evidências do desempenho de um processo de economia de escala no sistema de produção de cana-de-açúcar. Palavras-chave: levantamento mecanizado de frota; economia de escala; cana de açúcar